A Framework for the Systemic Implementation of Differentiated Instruction: A Case Study from Madrasah Tsanawiyah Al Abror - Muhammad Zuhaery; Achadi Budi Santosa; Edhy Susatya (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze the organizational model for implementing differentiated instruction to achieve student learning mastery at Madrasah Tsanawiyah Al Abror, an Islamic junior high school in Indonesia. A qualitative case study design was employed, involving data collection through in-depth interviews, classroom observations, and a systematic analysis of curriculum documents conducted over four months. Ten key participants took part, including the principal, vice-principal for curriculum, and eight teachers. The findings reveal four interdependent pillars: first, the institutionalization of diagnostic assessments providing a data-driven foundation for instructional planning; second, the flexible implementation of differentiation in content, process, product, and learning environment to meet diverse student needs; third, continuous teacher competence development fostered through active Professional Learning Communities (PLCs); and fourth, the establishment of a supporting infrastructure via a shared repository of teaching materials. These pillars collectively form a sustainable ecosystem that enables teachers to respond effectively to the diversity of their students. The study concludes that successful differentiated instruction requires shifting the focus from individual teacher efforts to developing organizational capacity and collaborative culture at the school level.